CT-like images based on T1-weighted gradient echo MRI sequences for the assessment of fractures of the hand and wrist compared to CT - Hesse, N.; Feuerriegel, G. C.; Erber, B.; Reidler, P.; Gottfried, V.; Stohldreier, Y.; Schmitt, R.; Dietrich, O.; Gersing, A. S.; Spiro, J. E. (Skeletal radiology, 2024)
Objective To evaluate the performance of a 3D T1-weighted gradient-echo (3D T1GRE) computed tomography (CT)-like magnetic resonance imaging (MRI) sequence for detecting and assessing wrist and hand fractures compared to conventional CT. Methods Subjects with acute wrist or hand fracture in CT underwent additional 3 T MRI including a CT-like 3D T1GRE sequence and were compared to patients without fractures. Two radiologists assessed fracture morphology on both modalities according to the Arbeitsgemeinschaft Osteosynthese (AO) and graded image quality and diagnostic confidence on a 5-point Likert scale. Besides diagnostic test evaluation, differences in image quality and diagnostic confidence between CT-like MRI and CT were calculated using the Wilcoxon test. Agreement of AO classification between modalities and readers was assessed using Cohen’s Kappa. Results Twenty-eight patients with 43 fractures and 43 controls were included. Image quality (3D T1GRE 1.19 ± 0.37 vs. CT 1.22 ± 0.42; p = 0.65) and diagnostic confidence (3D T1GRE 1.28 ± 0.53 vs. CT 1.28 ± 0.55; p = 1.00) were rated excellent for both modalities. Regarding the AO classification, intra- (rater 1 and rater 2, κ = 0.89; 95% CI 0.80–0.97) and interrater agreement were excellent (3D T1GRE, κ = 0.82; 95% CI, 0.70–0.93; CT, κ = 0.85; 95% CI, 0.75–0.94). CT-like MRI showed excellent sensitivity, specificity and accuracy for fracture detection (reader 1: 1.00, 0.92, 0.96; reader 2: 0.98, 0.94, 0.96). Conclusion CT-like MRI is a comparable alternative to CT for assessing hand and wrist fractures, offering the advantage of avoiding radiation exposure.